Employee well-being and engagement in Anheuser-Busch InBev Czech s.r.o. - Naime Benítez, Gabriel; Hořáková, Marie; Legnerová, Kateřina, 1965-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This bachelor’s thesis investigates how job demands and job resources relate to employee engagement and well-being at Anheuser-Busch InBev Czech s.r.o. The goal is to describe current levels of engagement, well-being, and burnout-related indicators, identify key demands/resources, and translate findings into practical recommendations. The study applies a mixed-methods case study design. Quantitative data were collected through an anonymous online survey that measured engagement, demands, resources, and burnout indicators. Qualitative insight was added through asynchronous interviews to explain patterns and contextual factors. Results show moderately strong engagement and generally positive perceptions of job resources, alongside low-to-moderate burnout indicators. Peak-period workload and time pressure emerged as the most prominent demands. Supportive resources, such as recognition, belonging, learning opportunities, and employee voice, appeared to be important for coping and sustaining motivation. The thesis concludes that strengthening practical resources and improving process clarity can help maintain engagement and protect well-being, particularly during periods of high demand.
Vedoucí práce: Marie Hořáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses